Ograniczenia inwestycji Otwartych Funduszy Emerytalnych a zasada swobody przepływu kapitału w świetle orzeczenia TSUE w sprawie (C-271_09) Komisja przeciwko Rzeczpospolitej Polskiej - Kociubiński, Jakub (Kwartalnik Prawa Publicznego, 2012)
This paper seeks to provide detailed analysis of the relatively recent and certainly highly commented judgment of the European Court of Justice in case C-271/09 European Commission v. Republic of Poland. In its ruling the Court stated that Poland has failed to fulfil its obligations under Article 63 TFEU – Free movement of Capital. The provisions imposing limitations on investment of capital assets for open pension funds (OFE) have been found to be infringing aforementioned freedom of the internal market. Two main issues are subject to scrutiny. First, what policy-driven State’s measures could be justified through general exemption clause incorporated in every internal market freedom. Whether requirements of a internal policy could warrant cross-border restrictions. Second of the discussed points relates to other communautaire means that could serve as a justification for such State’s measures. “Escape Clause” encapsulated in Article 106(2) TFEU could be use a as “shield” against any EU provision but in order to use it a given entity (OFE) must be classed as undertaking entrusted in operations of services of general economic interest. This raises serious questions whether activities of a social security operator could be deemed economic and whether this field is subject to the rules of EU Law or the law of the Member States.